Real-Time Protein and Cell Binding Measurements on Hydroxyapatite Coatings - A. M. Vilardell; N. Cinca; A. Jokinen; N. Garcia-Giralt; S. Dosta; I. G. Cano; J. M. Guilemany (Journal of Functional Biomaterials, 2016)
Although a lot of in vitro and in vivo assays have been performed during the last few decades years for hydroxyapatite bioactive coatings, there is a lack of exploitation of real-time in vitro interaction measurements. In the present work, real-time interactions for a plasma sprayed hydroxyapatite coating were measured by a Multi-Parametric Surface Plasmon Resonance (MP-SPR), and the results were compared with standard traditional cell viability in vitro assays. MP-SPR is proven to be suitable not only for measurement of molecule–molecule interactions but also molecule–material interaction measurements and cell interaction. Although SPR is extensively utilized in interaction studies, recent research of protein or cell adsorption on hydroxyapatite coatings for prostheses applications was not found. The as-sprayed hydroxyapatite coating resulted in 62.4% of crystalline phase and an average thickness of 24 ± 6 μm. The MP-SPR was used to measure lysozyme protein and human mesenchymal stem cells interaction to the hydroxyapatite coating. A comparison between the standard gold sensor and Hydroxyapatite (HA)-plasma coated sensor denoted a clearly favourable cell attachment on HA coated sensor as a significantly higher signal of cell binding was detected. Moreover, traditional cell viability and proliferation tests showed increased activity with culture time indicating that cells were proliferating on HA coating. Cells show homogeneous distribution and proliferation along the HA surface between one and seven days with no significant mortality. Cells were flattened and spread on rough surfaces from the first day, with increasing cytoplasmatic extensions during the culture time.